From Myth to Contemporaneity: A Study of Gender Identity and Split Personality in Girish Karnad’s Nagamandala and The Fire and the Rain - Dr Amrita Ghosh (The Creative Launcher, 2018)
Girish Karnad presents the individual as well as social predicaments, resulting from the dichotomy between instinct and reason, body and mind, male and female psyche in his plays like Nagamandala and The Fire and the Rain. In Karnad’s plays, while the female characters search for a completeness within their partners, the men fail to achieve a harmonious existence of their body and mind. Karnad’s plays become aesthetic experiences, which release multiple connotations with their rootedness in human emotions and instinct. Nagamandala as well as The Fire and the Rain becomes universal, timeless plays, where myth and reality, fact and fiction get fused in order to unravel the complex, discursive demands of contemporary socio-cultural paradigm. The plots of these two plays, Nagamandala and The Fire and the Rain are drawn from myths and folk tales. Karnad, for whatever the causes may be, derives the plot of most of his plays from pre-existing materials like myths, legends, folklore, history, yet like any great craftsman like Shakespeare, he transforms the raw material into a unique drama of human emotions and feelings. Karnad recreates, adapts and relates these mythic as well as the folkloric tales in order to relate them to the predicament of split personality of modern man. These plays also latently manifest Karnad’s concern with the issue of gender identity. Karnad’s plays are, thus, not mere imitations of life, but are representations of existential predicament and concretizations of philosophical abstractions.